Analysis of the Soundness Level of Islamic People's Financing Banks in Indonesia - Asrina, Putri; Misdawita, Misdawita; Kurniasih, Cut Endang (Adpebi International Journal of Multidisciplinary Sciences, 2023)
This study aims to analyze and determine the health level of Islamic Rural Bank (BPRS) in Indonesia from 2017-2021 before and during the Covid-19 pandemic. The method used is the Paired Sample t Test and the Wilcoxon signed Rank Test on indicators of the soundness level of the BPRS, including Finance to Deposit Ratio (FDR), Capital Adequacy Ratio (CAR), Non Performing Finance (NPF), Ratio of Operating Expenses to Operating Income (BOPO), Return On Assets (ROA) and Return On Equity (ROE). The results of the research based on the Paired Sample T test found that there was a significant difference in the FDR variable before and during the Covid-19 pandemic. Meanwhile, the results of the Wilcoxon signed rank test showed that there were significant differences between CAR, NPF, BOP, ROA and ROE before and during the Covid-19 pandemic